Viabilidade econômica do cultivo de oliveira na região da Secretaria de Desenvolvimento regional de São Miguel do Oeste-SC - Dorigon, Vandecir (2011)
RACT: The study of viability on cultivation of olive trees has shown that you can get profitability together with sustainability in small farms in seven counties that belong to Department of Regional Development of São Miguel do Oeste, Santa Catarina State, Brazil. The olive tree is an alternative to replacement planting of commodities in the region, since it is not economically feasible on a small scale, and characteristic of this region are small farms using family labor. Once the planting of olive trees can be established in areas of protection, without infringing environmental legislation, and increase family income. Data were obtained from literature searches and experiential, was subsequently carried out detailed economic viability study based on cost and yield on 01 hectare of crop. Thus, analyzes that in 10 years of production, olive has accumulated surplus of R$ 172.638,00, approximately 44% more than the tobacco culture. Besides the economic gains are larger in the cultivation of olive compared with tobacco growing, we can also mention the social and environmental gains, difficult to measure, but that can be seen in the quality of life of people who practice healthy habits.